Safety and efficacy of the minilaparotomy for myomectomy: a systematic review and meta-analysis of randomized and non-randomized controlled trials. Issue 5 (May 2015) - Palomba, Stefano; Fornaciari, Eleonora; Falbo, Angela; La Sala, Giovanni Battista
Abstract Myomectomy is the most frequent reproductive surgery to preserve, improve fertility, or both. The present study was designed to assess the safety and efficacy of minilaparotomy for myomectomy through a systematic review of randomized and non-randomized controlled trials with a meta-analysis. All available studies comparing minilaparotomy myomectomy with laparotomy, other minimally invasive surgeries, or both, were included. Available surgical and reproductive data were extrapolated, and a qualitative and quantitative analysis was carried out. Fourteen studies were included in the final analysis for an overall sample of 2151 patients. A total of 1139 patients were treated with minilaparotomy, whereas 239 and 773 patients were treated, respectively, with the laparotomy or laparoscopy. Only two studies comparing minilaparotomy with laparoscopy assessed the reproductive outcomes, and their data synthesis did not demonstrate significant difference between the two surgical techniques. Specific surgical end-points differed significantly between minilaparotomy and laparotomy or laparoscopy, even if those differences were not clinically relevant. In conclusion, current data do not permit a definite conclusion to be drawn. Further studies are needed to clarify the risk–benefit ratio of the minilaparotomy compared with the other minimally invasive surgical procedures for myomectomy to provide clinical recommendations with strong scientific evidence.